Uruguay : Seventh Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criterion-Staff Report and Supplement; Press Release; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report ;, 2005)
This paper assesses Uruguay's Seventh Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criterion. The favorable program results reflect prudent macroeconomic policies and important banking reforms, although progress with other structural reforms was less satisfactory. The outlook for 2005 is favorable. Growth will likely exceed 5 percent, and inflation is expected to fall to 5 1\2 -6 1\2 percent. A strong foundation has been laid for continued fiscal consolidation. The pending reforms under the current program will need to be taken up by the new government.